2021
DOI: 10.25165/j.ijabe.20211405.6072
|View full text |Cite
|
Sign up to set email alerts
|

Influences of moisture content and compressive loading speed on the mechanical properties of maize grain orientations

Abstract: Determination of the mechanical properties (rupture force, deformation, hardness, and toughness) of maize grain could be a significant concern for designing the harvester, thresher, and handling, processing, and storage equipment. Thus, the present research was conducted to assess the vertical and lateral rupture force, deformation, hardness, and toughness of maize grain (Beijing Denong, Lianchuang, Suyu 20, Liyu 88 and Suyu 29) influenced by different moisture contents (11.2%, 17.5%, and 21.3%) and compressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…The grains such as corn, rice, wheat, and soybean are materials that shows more elastic and plastic behaviour than the brittle inorganic materials [ 72 , 73 ]. It was shown that most agricultural materials reveal elastic behaviour in the first loading part, and with the increased loading, the properties change into viscoelastic [ 74 ]. In addition, the behaviour and impact resistance of the grains changes with several properties such as grain size, strength, vitreousness, the internal structure (including the share of starch, and protein), hardness, and moisture content [ 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The grains such as corn, rice, wheat, and soybean are materials that shows more elastic and plastic behaviour than the brittle inorganic materials [ 72 , 73 ]. It was shown that most agricultural materials reveal elastic behaviour in the first loading part, and with the increased loading, the properties change into viscoelastic [ 74 ]. In addition, the behaviour and impact resistance of the grains changes with several properties such as grain size, strength, vitreousness, the internal structure (including the share of starch, and protein), hardness, and moisture content [ 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference in moisture, protein, and starch content would cause the difference in endosperm hardness. Usually, the harder endosperm had lower moisture content and higher protein content (Budny et al, 2016; Chandio et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These models were selected based on their previous successful application in describing the relationship between moisture content and physical properties in various grains and seeds. Notably, these models have been used in studies related to flaxseeds (Singh, 2016), corn (Chandio et al, 2021;Coşkun et al, 2006;Karababa and Coşkuner, 2007;Sangamithra et al, 2016;Sobukola et al, 2013), velvet beans (Adeyanju et al, 2022), pinto beans (Santos et al, 2016), and sesame seeds (Eze et al, 2022;Tunde Akintunde and Akintunde, 2007). The coefficient of determination (R 2 ) was adopted as a measure for goodness of fit, with higher R 2 values indicating a higher quality of model fitness to the experimental data.…”
Section: Simple Regression Analysis and Prediction Of Engineering Pro...mentioning
confidence: 99%